Mandibular arch orthodontic treatment stability using passive self-ligating and conventional systems in adults: A randomized controlled trial - Ab Rahman, N.; Wey, M.C.; Othman, S.A. (Korean Association of Orthodontists, 2017)
Objective: This randomized controlled trial aimed to compare the stability of mandibular arch orthodontic treatment outcomes between passive self-ligating and conventional systems during 6 months of retention. Methods: Forty-seven orthodontic patients with mild to moderate crowding malocclusions not requiring extraction were recruited based on inclusion criteria. Patients (mean age 21.58 +/- 2.94 years) were randomized into two groups to receive either passive self-ligating (Damon (R) 3MX, n = 23) or conventional system (Gemini MBT, n = 24) orthodontic treatment. Direct measurements of the final sample comprising 20 study models per group were performed using a digital caliper at the debonding stage, and 1 month, 3 months, and 6 months after debonding. Paired t-test, independent t-test, and non-parametric test were used for statistical analysis. Results: A significant increase (p < 0.01) in incisor irregularity was observed in both self-ligating and conventional system groups. A significant reduction (p < 0.01) in second interpremolar width was observed in both groups. Mandibular arch length decreased significantly (p = 0.001) in the conventional system group but not in the self-ligating system group. A similar pattern of stability was observed for intercanine width, first interpremolar width, intermolar width, and arch depth throughout the 6-month retention period after debonding. Comparison of incisor irregularity and arch dimension changes between self-ligating system and conventional system groups during the 6 months were non-significant. Conclusions: The stability of treatment outcomes for mild to moderate crowding malocclusions was similar between the selfligating system and conventional system during the first 6 months of retention.